Creative City Making as a Theoretical Research Practice by Using Soft Systems Methodology - Maryunani, Salfitrie; Simatupang, Togar; Mirzanti, Isti (Journal of Urban Culture Research, 2025)
This study proposes a novel conceptual framework for creative city development that integrates cultural and economic perspectives, moving beyond the traditional singular focus of existing literature. It identifies three core variables – culture, creativity, and the creative economy – within a balanced model. Using Soft Systems Methodology (SSM) as a structuring tool, the framework conceptualizes these interrelations within a complex urban system. Its originality is demonstrated through a design for application in Bandung, Indonesia, an underexplored context, providing a foundation for empirical validation. The paper concludes with actionable activities for implementation, offering a comprehensive tool for integrated diagnosis and planning by researchers and policymakers.